Mental symptoms in patients with cardiac symptoms and normal coronary arteries. Issue 1 (3rd November 2014) - Christoph, Marian; Christoph, Antje; Dannemann, Stephanie; Poitz, David; Pfluecke, Christian; Strasser, Ruth H; Wunderlich, Carsten; Koellner, Volker; Ibrahim, Karim
Abstract : Objectives: Patients with chest pain and normal coronary arteries often suffer from physical and psychological symptoms. Therefore, this study aimed to examine the incidence of mental symptoms in patients with angiographic exclusion of a coronary heart disease. Design: In 253 patients with angiographic exclusion of a coronary heart disease the type and intensity of their symptoms were evaluated before and after coronary angiography. In addition, the incidence of psychopathological symptoms was quantified by standardised questionnaires such as general anxiety and depression (HADS), heart-focused anxiety (CAQ), hypochondria (Whiteley Index) and somatoform disorder (SOMS) and quality of life (SF-12). Finally, the incidence of psychological symptoms in these patients was compared to the incidence in the normal population. Results: Despite the absence of a coronary artery disease, 70% of patients continue to suffer from cardiac symptoms. The incidence of general anxiety was increased by 37% in women and by 22% in men in comparison to the normal population. Heart-focused anxiety was raised by 27%. Somatoform disorder appeared 120% more often in patients after cardiac catheterisation in comparison to the normal population. In addition, the incidence of hypochondria was elevated by 68% in patients after coronary angiography compared to normal population. This increased appearance of psychological symptoms was reflected in a significantly lower quality of life (SF-12) in patients with inconspicuous coronary angiography. Conclusions: Patients with cardiac symptoms and normal coronary arteries more often suffer from mental symptoms in comparison to the healthy population.